Impact of structural variables on hydroenergetic efficientization of water pumping system (Research, Society and Development, 2020)
Evaluate the structural variables influence on the consumption and the electrical energy cost from Guamá river’s Water Pumping System (WPS) located in Belém city (Pará), through Plackett and Burman experimental planning, computational simulations and of statistical analysis. This present study was divided into four stages. In Step 1, it was carried out the design characterization and limits determination (minimum and maximum) of the variables geometric height, diameter and pressurized pipes length and stand pipe reservoir useful volume. Then (Step 2) it was applied the Plackett and Burman experimental planning, in order to define the number of tests to be simulated. In Step 3, it was held hydraulic simulations of different operational routines, to determine the consumption and electric power cost in the WPS. The last stage was accomplished statistical analysis (Hypothesis test and Pareto Diagram) for a 95% significance level. Based on the results, the structural variables that most impacted upon the consumption and the WPS electricity cost Guamá River were the useful volume daily required, followed by the pressurized pipe diameter. From the experimental planning technique application, the sanitation manager will be able to prioritize the energy efficiency actions of the investigated system.